1999
DOI: 10.1021/es981221w
|View full text |Cite
|
Sign up to set email alerts
|

Local Motions of Organic Pollutants in Soil Components, as Studied by 2H NMR

Abstract: 2 H NMR spectra and interpretations are presented on a series of samples, each consisting of a deuterium-labeled organic pollutant (trichloroethylene, acetone, pyridine, benzene, or ethylene glycol) adsorbed on a soil component (montmorillonite clay or humic acid). Spectra were obtained over a wide temperature range and using two values of the quadrupolar echo delay period. Computer simulations of line shapes resulting from various forms of local motion of C-2 H moieties provide useful guidelines for interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…The cross polarization (CP) of magnetization from the abundant protons in polymers to the measured nuclei facilitates measurements of materials such as PBI or PAEK polymers, as it improves the signal to noise (S/N) ratio in the spectra [2,12e14]. The most common nucleus for measuring polymers is 13 C [12,13,20], followed by 2 H wideline (no spinning) and MAS (Magic Angle Spinning) NMR [10, 19,23]. In this contribution it will be demonstrated that 1 Mobile species lead to a relatively narrow signal sitting on the broad hump of the backbone signal in the 1 H wideline NMR spectra [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…The cross polarization (CP) of magnetization from the abundant protons in polymers to the measured nuclei facilitates measurements of materials such as PBI or PAEK polymers, as it improves the signal to noise (S/N) ratio in the spectra [2,12e14]. The most common nucleus for measuring polymers is 13 C [12,13,20], followed by 2 H wideline (no spinning) and MAS (Magic Angle Spinning) NMR [10, 19,23]. In this contribution it will be demonstrated that 1 Mobile species lead to a relatively narrow signal sitting on the broad hump of the backbone signal in the 1 H wideline NMR spectra [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium NMR studies have been used to quantify 113 Cd binding (Chung et al, 1996 ;Larive et al, 1996 ;Otto et al, 2001b ), evaluate chemical exchange (Larive et al, 1996 ), identify the groups (mainly oxygen, but also nitrogen and sulfur at certain pH values) responsible for binding (Hertkorn et al, 2004 ), and identify specifi c (inner/outer sphere) complexes (Grassi and Daquino, 2005 ). Similarly, in the area of organic contaminant interactions, a wide array of studies have been performed (Thorn et al, 1996a(Thorn et al, ,b, 1997Bortiatynski et al, 1997 ;Hinedi et al, 1997 ;Jayasundera et al, 1997 ;Nanny et al, 1997 ;Achtnich et al, 1999 ;Dixon et al, 1999 ;Green et al, 1999 ;Knicker et al, 1999 ;Nanny, 1999 ;Xiong et al, 1999 ;Bruns -Nagel et al, 2000 ;Kohl et al, 2000 ;Emery et al, 2001 ;Smernik and Oades, 2001 ;Kacker et al, 2002 ;Thorn and Kennedy, 2002 ;Strynar et al, 2004 ;Smernik et al, 2006 ). Using NMR, it has been possible to determine the amount of organic contaminants bound (Simpson et al, 2004c ), evaluate binding type (covalent and noncovalent) (Nanny et al, 1997 ;Achtnich et al, 1999 ;Nanny and Maza, 2001 ), extract mechanistic information (Wais et al, 1996 ;Hinedi et al, 1997 ), and even focus on the structural components of NOM involved .…”
Section: Contaminant Interactionsmentioning
confidence: 99%
“…Contaminants that contain quadrapolar nuclei such as deuterium are also well -suited to NMR studies. Nanny has demonstrated that noncovalent interactions between NOM and deuterated contaminants can be carried out in solution (Nanny, 1999 ;Nanny and Maza, 2001 ), while other studies have monitored the quadrapolar lineshape of deuterated contaminants as a sensitive probe to their environment in solid -state NMR (Xiong et al, 1999 ;Emery et al, 2001 ). Paramagnetic species can induce fast relaxation of species in close proximity.…”
Section: Other Approachesmentioning
confidence: 99%
“…Isotropic motion (ISO) is modeled with 32 sites in which the C-D bond is oriented along an axis from the center to each one of the 20 face centers and 12 vertices of an icosahedron [5,6]. This model was originally used with the AEE kinetic mode [6], but we also try AEU and NN modes. Methyl rotation (MeRot) is modeled with three sites with angle of 70.5°between the C-D bond and the threefold rotation axis [10].…”
Section: Motional Models and Calculationsmentioning
confidence: 99%
“…Deuterium quadrupole echo spectra have been used to study dynamics of many systems including macromolecules [1], small molecular complexes [2], and small molecules in association with substrates such as zeolites [3], silica [4] or clay [5,6]. The shape of the quadrupole echo spectrum is generally sensitive to motions with a range of rates from 10 3 to 10 7 s À1 [7].…”
Section: Introductionmentioning
confidence: 99%